PENGARUH PERCEIVED VALUE DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI PADA TOKO JAKARTA CLOTH SITUBONDO - Zaufariyanto, Abdul Malik; Soeliha, Siti; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The research objective is to determine the effect of perceived value and service quality on purchasing decisions through consumer satisfaction as a mediating variable at the Jakarta Cloth Situbondo store. The sampling technique used in this study was simple random sampling of 98 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Perceived value has a positive and significant effect on consumer satisfaction, service quality has a positive and significant effect on consumer satisfaction, perceived value has a positive and significant effect on purchasing decisions, service quality has a negative but not significant effect on purchasing decisions, consumer satisfaction has a positive and significant effect on purchasing decisions, perceived value has a positive but not significant effect on purchasing decisions through consumer satisfaction, service quality has a positive and significant effect on purchasing decisions through consumer satisfaction.